Clinical outcomes in U.S. infants with cystic fibrosis from 2001 to 2012. Issue 11 (26th September 2018) - Hoch, Heather; Sontag, Marci K.; Scarbro, Sharon; Juarez‐Colunga, Elizabeth; McLean, Cindie; Kempe, Allison; Sagel, Scott D.
Abstract: Background: All 50 United States implemented newborn screening (NBS) for cystic fibrosis (CF) by 2010. The purpose of this study was to evaluate trends over the decade when NBS became universal to determine current rates of malnutrition, stunting, and infection rates in U.S. infants with CF. Methods: Annual data were obtained on infants with CF up to 24 months of age diagnosed between 2001 and 2010 in the CF Foundation Patient Registry (CFFPR), in both the years of and after diagnosis, including method of diagnosis, demographics, and growth parameters and microbiology. Results: Data were obtained on 8178 infants diagnosed with CF. The percentage of infants diagnosed by NBS increased from 15% in 2001‐83% in 2012 ( P < 0.001). Mean weight, length, and weight‐for‐length z‐scores in the year of diagnosis increased from 2001 to 2012 (Wt z‐score 2001: −1.32 (SD 1.41), 2012: −0.72 (SD 1.12); Ht z‐score 2001: −1.32 (SD 1.57), 2012 −0.60 (SD 1.21); Wt/Ht Z score 2001: −0.54 (SD 1.18), 2012: 0.06 (SD 1.05); P < 0.001 for each). The proportion of infants on pancreatic enzymes decreased from 94% in 2001‐83% in 2012 ( P < 0.0001). Pseudomonas aeruginosa culture positivity in the diagnosis year decreased significantly (27% in 2001, 15% in 2012, P < 0.001). Conclusions: Nationwide implementation of CF NBS is temporally associated with significant improvements in growth outcomes and reductions in P. aeruginosa infections. Current rates of malnutrition, stunting, and airway infection present a target for early intervention and quality improvement efforts.